2018
DOI: 10.1063/1.5016876
|View full text |Cite
|
Sign up to set email alerts
|

Chain length effects of p-oligophenyls with comparison of benzene by Raman scattering

Abstract: Raman scattering measurements are performed on benzene and a number of p-oligophenyls including biphenyl, p-terphenyl, p-quaterphenyl, p-quinquephenyl, and p-sexiphenyl at ambient conditions. The vibrational modes of the intra-and intermolecular terms in these materials are analyzed and compared. Chain length effects on the vibrational properties are examined for the C-H in-plane bending mode and the inter-ring C-C stretching mode at around 1200 cm −1 and 1280 cm −1 , respectively, and the C-C stretching modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The materials were also investigated via Raman spectroscopy (Figure C and Figure S3) where characteristic bands were observed at 1220 cm −1 (ν intra‐ring (C−C)), 1280 cm −1 (ν inter‐ring (C−C)), and 1600 cm −1 (δ in‐plane (C−H)) . Fitting the spectral peaks by a Lorentzian function and comparing the intensities of the peaks at 1220 cm −1 and 1280 cm −1 validated qualitatively the high degree of polymerization as calculated from FTIR. However, quantification was not possible with this technique, since the polymers were already too long (for further information see Section 4 in the Supporting Information) …”
Section: Methodsmentioning
confidence: 59%
“…The materials were also investigated via Raman spectroscopy (Figure C and Figure S3) where characteristic bands were observed at 1220 cm −1 (ν intra‐ring (C−C)), 1280 cm −1 (ν inter‐ring (C−C)), and 1600 cm −1 (δ in‐plane (C−H)) . Fitting the spectral peaks by a Lorentzian function and comparing the intensities of the peaks at 1220 cm −1 and 1280 cm −1 validated qualitatively the high degree of polymerization as calculated from FTIR. However, quantification was not possible with this technique, since the polymers were already too long (for further information see Section 4 in the Supporting Information) …”
Section: Methodsmentioning
confidence: 59%
“…Very recently, the comparative study of LF Raman spectra of oligophenyls ( n = 1–6) was reported in ref. . These spectra are presented in Figure b and show that the lowest‐frequency mode redshifts with n as in oligoacenes.…”
Section: Impact Of Molecular and Crystal Structure On Lf Vibrationsmentioning
confidence: 84%
“…, and for oligophenyls from ref. . For tetracene and pentacene, the spectra corresponding to the two stable crystal structures (LT and HT phases, see Section 4.2) are shown.…”
Section: Impact Of Molecular and Crystal Structure On Lf Vibrationsmentioning
confidence: 99%
“…The C-H in-plane bending modes and the interring C-C stretching modes located at around 1220 and 1280 cm −1 are common indicators to identify the molecular conjugations at ambient condition (chain length and planarity). 39,[50][51][52][53][54] The energy separation of these two modes increases with increasing phenyl ring number in one molecule. And the intensity ratio of the POPs monotonously declines, but the pace of the declines slows, it almost converges to zero for the infinite long polymer (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity ratio of these two modes are also always used to estimate the molecular conjugation. 39,50,55 However, due to the drastic splits of these peaks, it becomes more difficult to distinguish the peaks. Here we choose two peaks located at around 1600 cm −1 with the strongest intensities, then calculate the intensity ratios of the five materials, the temperature dependent intensity ratios between the lower energy peaks and the higher energy peaks of POPs are presented in Figs.…”
Section: Methodsmentioning
confidence: 99%